Making the scene : contemporary New York City big band jazz - Stewart, Alex, 1952- (Roth Family Foundation music in America imprint., 2007)
The received wisdom of popular jazz history is that the era of the big band was the 1930s and 40s, when swing was at its height. But as practicing jazz musicians know, even though big bands lost the spotlight once the bebop era began, they never really disappeared. Making the Scene challenges conventional jazz historiography by demonstrating the vital role of big bands in the on-going development of jazz. Identifying over eighty contemporary big bands in New York City alone, most of them hidden in plain sight, Alex Stewart describes how jazz musicians have found big bands valuable, not only as compositional and skill-building resources, but for making social contacts. In addition he explores the rich "rehearsal band" scene in New York and the rise of repertory orchestras. A rare example of a holistic approach to musicology, Making the Scene combines historical research, ethnography, and participant observation with musical analysis, ethnic studies, and gender theory, to demolish stereotypical views of the big band. A jazzman himself, Stewart shares insider perspectives on contemporary big bands such as the Vanguard, the Lincoln Center Jazz Orchestra, and the Mingus Big Band, along with such composers as Maria Schneider, Andrew Hill, Ray Santos, and Carla Bley. Setting a broad new standard for jazz studies, Making the Scene explores the creative interactions of composers and improvising musicians from avant-garde and Latin big bands to mainstream jazz orchestras.